On Finding Shortest Path Over Vocational High School in Yogyakarta Based on Graph Theory Algorithm - Rahmadi, Deddy (Universitas Negeri Padang, 2023)
Finding shortest path is one of problem in graph theory. This research aims to apply the Dijkstra algorithm in determining the shortest route for State Vocational School (SMK) students throughout Yogyakarta. State Vocational Schools throughout Yogyakarta have several locations spread across various regions, and determining the shortest path is crucial for the efficiency of students' time and transportation. Dijkstra's algorithm was chosen because of its ability to find the shortest path in a weighted graph, which can be applied to complex networks of school trajectories. The research method involved collecting geographic data on schools, available transportation, and distance between locations. This data is used to build a weighted graph that represents the transportation network between State Vocational Schools throughout Yogyakarta. The implementation of Dijkstra's algorithm is then carried out using python programming language. We hope that the research results can provide mapping of the shortest routes between schools, minimize student travel time, and increase transportation efficiency. The practical implications of this research include the development of an information system or application that can help students, teachers and schools in planning daily trips. Apart from that, the research results can also be a basis for developing methods for determining the shortest route in the context of other schools or similar environments.